The Impact of Adenotonsillectomy on the Quality of Life of Children with Obstructive Sleep Apnea - Sukumaran, Geethi Krishna; Sunanda, Asha Chellappan; George, Shajul (International Archives of Otorhinolaryngology, 2024)
Introduction In children, obstructive sleep apnea (OSA) is a sleep-related breathing disorder that is caused by adenotonsillar hypertrophy and is characterized by upper airway obstruction disturbing sleep.Objective We conducted this study to evaluate health-related quality of life (QoL) in children with OSA before and after adenotonsillectomy.Methods A descriptive, observational study was conducted among 43 children in the 4-to-12 years old age group who had symptoms of OSA due to adenotonsillar hypertrophy and who underwent adenotonsillectomy at a tertiary care center during the period from February 2020 to February 2021. The QoL was assessed using the OSA-18 questionnaire preoperatively and at 2 and 6 months postoperatively.Results Among the study population, males (72)%) were more affected with OSA, with a male-to-female ratio of 2.6:1. Based on the OSA-18 questionnaire assessment, the most severe and frequently observed symptoms were in the domains of sleep disturbance and physical symptoms, in which the mean score was 77 preoperatively. After adenotonsillectomy, the mean OSA-18 score decreased to 28.605 and 22.465 at 2 and 6 months, respectively. At 2 months postsurgery, more significant improvement was noticed in sleep disturbances, physical symptoms, and parent's concern while at 6 months postsurgery, all domains showed equal improvement. Therefore, following adenotonsillectomy, the QoL improved significantly.Conclusion Obstructive sleep apnea can adversely affect sleep quality as well as neurocognitive and cardiovascular functions. Adenotonsillectomy resulted in significant improvement in the QoL.
Keywords: adenoidectomy; tonsillectomy; sleep apnea; obstructive; quality of life